HOW PERINATAL HYPOXIA INDUCES APOPTOSIS IN THE CARDIOMYOCYTES OF NEWBORN - Zadnipryany, I.V.; Tretjakova, O.S.; Sataieva, T.P. (World of Medicine and Biology, 2014)
In the heart of newborn intrauterine hypoxia contributes into development of reversible and in severe cases irreversible changes in cardiomyocytes (conducting and contractile) and in microcirculatory vessels which is a manifestation of not only hypoxic damage of the heart muscle but also evidence of ischemic nature of myocardial damage. In the early stages of ischemia apoptosis is the predominant form of death of cardiomyocytes. Typical apoptosis reaction in posthypoxic cardiomyopathy is strengthening of its mitochondrial route. Proved that chronic heart failure in children is accompanied by activation of all parts of programmed cell death, while the severity of apoptosis induction depends on the stage of heart failure.